2017
DOI: 10.1104/pp.17.01152
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Arabidopsis MAP Kinase Phosphatase 1 (MKP1) Is Required for PAMP Responses and Resistance against Bacteria

Abstract: Plants perceive potential pathogens via the recognition of pathogen-associated molecular patterns (PAMPs) by surface-localized pattern recognition receptors, which initiates a series of intracellular responses that ultimately limit bacterial growth. PAMP responses include changes in intracellular protein phosphorylation, including the activation of mitogen-activated protein kinase (MAPK) cascades. MAP kinase phosphatases (MKPs), such as Arabidopsis (Arabidopsis thaliana) MKP1, are important negative regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Previous studies in non-enterocyte cell lines implicated ERK-dependent phosphorylation at the non-catalytic C-terminal domain of Mkp-1 as a modulator of its degradation. As some studies found ERK phosphorylation accelerating 14, 18, 20, 21 , and others delaying Mkp-1 degradation 12, 13, 23, 24, 26, 27 , the role of phosphorylation remains controversial. In the epithelium of rat small intestine, both Mkp-1 and activated ERK localize to crypts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in non-enterocyte cell lines implicated ERK-dependent phosphorylation at the non-catalytic C-terminal domain of Mkp-1 as a modulator of its degradation. As some studies found ERK phosphorylation accelerating 14, 18, 20, 21 , and others delaying Mkp-1 degradation 12, 13, 23, 24, 26, 27 , the role of phosphorylation remains controversial. In the epithelium of rat small intestine, both Mkp-1 and activated ERK localize to crypts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the PTMs of MAPK cascades mediated by effectors, several phosphatases that negatively regulate these MAPK cascades have been reported. Dual-specificity MAP kinase phosphatases (MKPs), such as MKP1 and MKP2, dephosphorylate both conserved Thr and Tyr residues of the MAPK activation loop, leading to the full inactivation of the MAPKs [95,96,97]. Furthermore, it is suggested that an efficient negative feedback loop exists between MKPs and MAPKs during PAMP responses and bacterial resistance [96].…”
Section: Ptms Of Rlck–mapk Are Required For Immune Signal Transducmentioning
confidence: 99%
“…Interestingly, different expression patterns of wheat TMKP1 were observed between different wheat cultivars with induced expression in sensitive cultivars and repressed in tolerant ones (Zaïdi et al, 2010 ). In contrast, the expression of Arabidopsis MKP1 does not appear to be significantly altered after exposure to either UV-B treatment or pathogen infection (González Besteiro and Ulm, 2013 ; Jiang et al, 2017a ), suggesting that MKP1 is mainly under post-translational regulation. Although the regulation of the IBR5 's transcription has not been reported, it has been shown that IBR5 is post-transcriptionally regulated, generating two transcripts, AT2G004550.1 and AT2G04550.3 , by alternative splicing to produce two IBR5 isoforms IBR5.1 and IBR5.3 (Jayaweera et al, 2014 ).…”
Section: Regulatory Mechanisms Of Dual Specificity Mapk Phosphatasesmentioning
confidence: 99%
“…For instance, the phosphatase activity of tobacco NtMKP1 is also increased by co-incubation of its substrates such as SIPK (Katou et al, 2005 ), and the catalytic activity of wheat TMKP1 is significantly enhanced by co-incubation of TMPK3 (Zaïdi et al, 2010 ). In addition to in vitro studies, in vivo studies using Arabidopsis transgenic lines expressing MKP1 protein have also shown that MKP1 is phosphorylated in response to both UV-B treatment and pathogen challenges (González Besteiro and Ulm, 2013 ; Jiang et al, 2017a ). The phosphorylation of MKP1 contributes to its stability and is required for its biological function during both UV-B stresses and pathogen infection (González Besteiro and Ulm, 2013 ; Jiang et al, 2017a ).…”
Section: Regulatory Mechanisms Of Dual Specificity Mapk Phosphatasesmentioning
confidence: 99%
See 1 more Smart Citation